2016
DOI: 10.1055/s-0042-107675
|View full text |Cite
|
Sign up to set email alerts
|

Pregnane Glycosides from Cynanchum marnierianum Stimulate GLP-1 Secretion in STC-1 Cells

Abstract: In the framework of the search for natural glucagon-like peptide-1 secretagogues, the bioassay-guided fractionation of the ethanolic extract from Cynanchum marnierianum led to the isolation of two new pregnane glycosides named marnieranosides A (1) and B (2). The structures were determined based on spectroscopic data and were established as 12β,20 S-O-dibenzoyl-pregn-6-en-5α,8β,14β,17β-tetraol-3-O-β-D-oleandropyranosyl-(1 → 4)-β-D-cymaropyranoside (1) and 12β,20R-O-dibenzoyl-pregn-6-en-5α,8β,14β-triol-3-O-β-D-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
1
10
1
Order By: Relevance
“…All compounds were found to be non-cytotoxic according to the MTS assay, with a cell viability superior to 90%. Regarding the GLP-1 secretagogue effect, none of the compounds stimulated the secretion of GLP-1 in STC-1 cells (values similar to the vehicle), as opposed to the previously assessed 12,20-O-dibenzoyl or 12-Otigloyl 2,6-dideoxyhexose pregnane glycosides [1]. This observation could indicate the necessity of the 12-O acylation and the presence of a dideoxyhexose chain linkage to the pregnane structure to stimulate the secretion of GLP-1.…”
Section: Resultscontrasting
confidence: 65%
See 2 more Smart Citations
“…All compounds were found to be non-cytotoxic according to the MTS assay, with a cell viability superior to 90%. Regarding the GLP-1 secretagogue effect, none of the compounds stimulated the secretion of GLP-1 in STC-1 cells (values similar to the vehicle), as opposed to the previously assessed 12,20-O-dibenzoyl or 12-Otigloyl 2,6-dideoxyhexose pregnane glycosides [1]. This observation could indicate the necessity of the 12-O acylation and the presence of a dideoxyhexose chain linkage to the pregnane structure to stimulate the secretion of GLP-1.…”
Section: Resultscontrasting
confidence: 65%
“…The GLP-1 secretion assay was carried out according to the previously published protocol [1]. Briefly, STC-1 cells were cultured in DMEM medium supplemented with 10% FBS, 100 U/mL penicillin, and 100 μg/L streptomycin, at 37°C in 5% CO 2 .…”
Section: Cell Culture Glp-1 Secretagogue Assays and Cell Viabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, we previously discovered that two pregnane glycosides from Cynanchum marnierianum (Apocynaceae), marnieranosides A and B, significantly stimulate GLP-1 secretion of intestinal secretin tumour cells (STC-1) (Tsoukalas et al, 2016). We also demonstrated that P57, a polyhydroxylated pregnane glycoside from Hoodia gordonii, possesses a similar activity in this bioassay.…”
Section: Introductionmentioning
confidence: 68%
“…With their unique structural features and significant diverse bioactivities [1], pregnane glycosides have attracted our attention. Immunosuppressive [2], anti-inflammatory [3], anti-epileptic [4], neuroprotective [5], anti-hyperglycemic [6], and cytotoxic [7] activities have been reported for pregnane glycosides, which show great potential as leads in medicine. Epigynum cochinchinensis (Pierre) D.J.…”
mentioning
confidence: 99%